State of commercial arbitration in Tanzania: a comparative study with Uganda - Musingi, Lilian Richard (Department of Commercial Law, 2025)
In general terms arbitration is the determination of dispute by the decision of one or more persons called arbitrators. It is an alternative means of dispute resolution to litigation. In arbitration parties have a say in the decision as to who should be involved in the determination of the dispute between them unlike in litigation where parties besides deciding on where to file a case which depends on the jurisdiction (territorial and pecuniary) of the courts, have no say not even influence on who should preside in their cases. In arbitration parties are also involved in deciding the venue of the arbitration. It is a voluntary procedure, also enforceable where parties to the dispute enter into an agreement that in case a dispute arises out of their commercial relationship, arbitration would be the mode of settling it. This means that the parties enter agreement selecting arbitration as mechanism to settle their dispute. Arbitration can be also ordered by the court on the application of the parties to the dispute. Its central features are that it is based on an agreement between the parties to the dispute, involves referral of a dispute to an independent arbitral tribunal (made up of one or more arbitrators) and produces a binding decision which may be enforced through the courts.